2007
DOI: 10.1359/jbmr.061016
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Population-Based Study Shows No Association Between Common Polymorphisms of the TGFB1 Gene and BMD in Women

Abstract: The TGFB1 gene is a strong functional candidate for regulating genetic susceptibility to osteoporosis. We studied five common polymorphisms of TGFB1 in relation to osteoporosis-related phenotypes in a population-based cohort of 2975 British women, but found no significant association with bone mass, bone loss, bone markers, or fracture. Introduction:The gene encoding TGFB1 is a strong functional candidate for genetic susceptibility to osteoporosis. Several polymorphisms have been identified in TGFB1, and previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
2
7
0
2
Order By: Relevance
“…As examples, the frequencies of the -509T and 869C alleles among controls in our study were 0.523 and 0.524, respectivelyvalues similar to those observed in healthy Japanese subjects (Kamiya et al, 2001;Kawaguchi et al, 2003) but higher than those in white subjects (McGuigan et al, 2007;Langdahl et al, 2003Langdahl et al, , 2008. We showed that the genotype distributions of SNP-509C>T and SNP 869T>C in controls are indeed in Hardy-Weinberg equilibrium, suggesting that the genetic structure of our sample is comparable to that of other studies of TGF-β1 polymorphism in OPLL patients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As examples, the frequencies of the -509T and 869C alleles among controls in our study were 0.523 and 0.524, respectivelyvalues similar to those observed in healthy Japanese subjects (Kamiya et al, 2001;Kawaguchi et al, 2003) but higher than those in white subjects (McGuigan et al, 2007;Langdahl et al, 2003Langdahl et al, , 2008. We showed that the genotype distributions of SNP-509C>T and SNP 869T>C in controls are indeed in Hardy-Weinberg equilibrium, suggesting that the genetic structure of our sample is comparable to that of other studies of TGF-β1 polymorphism in OPLL patients.…”
Section: Discussionsupporting
confidence: 87%
“…The T allele of the -509C>T polymorphism is associated with reduced bone mass in postmenopausal Japanese women (Yamada et al, 2001) and in white men (Langdahl et al, 2008), whereas the T allele is associated with increased BMD in Danish men and women (Langdahl et al, 2003). Another study has shown no association between the -509C>T polymorphism and BMD or bone loss in a British population (McGuigan et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Lau et al (33) conducted a study on the polymorphism of TGF-b1 in postmenopausal women, showing that serum OC and uNTX levels were significantly increased in a comparison between the TC genotype and TT or CC genotype, but the differences in serum TGF-b1 level among these genotypes were not statistically significant. McGuigan et al (34) conducted large-scale investigations on the female population,…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in TGFB1 cause autosomal dominant Camurati-Engelmann disease, a rare condition characterized by increased BMD that predominantly aVects the long bones of the arms and legs (Janssens et al 2000). Several studies prior to 2007 analyzed common TGFB1 SNPs with respect to BMD and osteoporotic fracture but yielded conXicting results (see McGuigan et al 2007b;Langdahl et al 2008 for references). Two recent studies genotyped the same Wve common SNPs in the TGFB1 gene in 2,975 women from the UK (McGuigan et al 2007b) and 28,924 subjects from 10 European research studies ), respectively; both indicated that none of the studied SNPs were generally associated with BMD or fracture risk.…”
Section: Tgfb1mentioning
confidence: 99%
“…Several studies prior to 2007 analyzed common TGFB1 SNPs with respect to BMD and osteoporotic fracture but yielded conXicting results (see McGuigan et al 2007b;Langdahl et al 2008 for references). Two recent studies genotyped the same Wve common SNPs in the TGFB1 gene in 2,975 women from the UK (McGuigan et al 2007b) and 28,924 subjects from 10 European research studies ), respectively; both indicated that none of the studied SNPs were generally associated with BMD or fracture risk. In addition, Huang et al (2009a) genotyped three TGFB1 SNPs in 1,243 Chinese subjects and also did not Wnd an association with BMD.…”
Section: Tgfb1mentioning
confidence: 99%